Enhanced drug delivery and wound healing potential of berberine-loaded chitosan–alginate nanocomposite gel: characterization and in vivo assessment - Akhter, Md Habban; Al-Keridis, Lamya Ahmad; Saeed, Mohd; Khalilullah, Habibullah; Rab, Safia Obaidur; Aljadaan, Adel M.; Rahman, Mohammad Akhlaquer; Jaremko, Mariusz; Emwas, Abdul-Hamid; Ahmad, Sarfaraz; Alam, Nawazish; Ali, Md Sajid; et al. (Frontiers in Public Health, 2023)
Berberine–encapsulated polyelectrolyte nanocomposite (BR–PolyET–NC) gel was developed as a long-acting improved wound healing therapy. BR–PolyET–NC was developed using an ionic gelation/complexation method and thereafter loaded into Carbopol gel. Formulation was optimized using Design-Expert® software implementing a three-level, three-factor Box Behnken design (BBD). The concentrations of polymers, namely, chitosan and alginate, and calcium chloride were investigated based on particle size and %EE. Moreover, formulation characterized in vitro for biopharmaceutical performances and their wound healing potency was evaluated in vivo in adult BALB/c mice. The particle distribution analysis showed a nanocomposite size of 71 ± 3.5 nm, polydispersity index (PDI) of 0.45, ζ–potential of +22 mV, BR entrapment of 91 ± 1.6%, and loading efficiency of 12.5 ± 0.91%. Percentage drug release was recorded as 89.50 ± 6.9% with pH 6.8, thereby simulating the wound microenvironment. The in vitro investigation of the nanocomposite gel revealed uniform consistency, well spreadability, and extrudability, which are ideal for topical wound use. The analytical estimation executed using FT-IR, DSC, and X-ray diffraction (XRD) indicated successful formulation with no drug excipients and without the amorphous state. The colony count of microbes was greatly reduced in the BR–PolyET–NC treated group on the 15th day from up to 6 CFU compared to 20 CFU observed in the BR gel treated group. The numbers of monocytes and lymphocytes counts were significantly reduced following healing progression, which reached to a peak level and vanished on the 15th day. The observed experimental characterization and in vivo study indicated the effectiveness of the developed BR–PolyET–NC gel toward wound closure and healing process, and it was found that >99% of the wound closed by 15th day, stimulated via various anti-inflammatory and angiogenic factors.